White collar crime : the uncut version - Sutherland, Edwin Hardin 1883-1950 (Yale University Press, 1983)
A classic study of corporate crime in America, now available for the first time the way Sutherland originally wrote itÑwith names and case studies of the offenders included.\ÒNow that corporate crime has become a documented tradition of widespread scope, SutherlandÕs proper name data can be released to fill out this remarkable and courageous work of criminological scholarship.ÓÑRalph Nader\ÒA scholarly and scalding examination of business and criminology, with an informative introduction.ÓÑNewsday\ÒThe book contains an excellent introduction by Geis and Goff and reveals, in vivid detail, the corporate looting, price-fixing cartels, union busting, and wartime profiteering engaged in by the most famous names of American businessÉ. The new data transforms a pioneering, well-written É book into a riveting combination of powerful criminological analysis and history of American corporate malfeasance in the first half of this century.ÓÑMichael Levi, The Times Higher Education Supplement\ÒDaring as it was when published, SutherlandÕs monograph is perhaps more relevant and important today, when crimes of the upper world may be more costly and poisonous to the soul than the crimes of the underworld.ÕÑWarren Bennis, Los Angeles Times Book Review